Factors influencing Human Papillomavirus Vaccination intention in Female High School Students: Application of Planned Behavior Theory - Min Hee Sung; Mi Hae Sung (Korean Society of Women Health Nursing, 2018)
PURPOSE: The purpose of this study was to identify effects of attitude, subjective norm, and perceived behavior control toward Human Papillomavirus (HPV) on HPV vaccination intention in female high school students. METHODS: Subjects of this study were female students aged 16 to 17 years, the optimal age group of HPV vaccination, arbitrarily selected from three high schools in B city. A total of 140 students agreed to participate in this study. Data were analyzed using descriptive statistics, t-test, ANOVA, correlation, and stepwise multiple regression. RESULTS: Attitude, subjective norm, and perceived behavior control toward HPV were factors influencing HPV vaccination intention of subjects. Perceived behavior control toward HPV vaccination was the most influential factor. These factors accounted for 49% of HPV vaccination intention. CONCLUSION: These results suggest a need to increase perceived behavior control to increase HPV vaccination intention. The government needs to establish a national policy system such as financial support for HPV vaccines and free vaccinations so that students are aware that HPV vaccines can be easily inoculated.